2010
DOI: 10.1210/me.2010-0010
|View full text |Cite
|
Sign up to set email alerts
|

GPR103b Functions in the Peripheral Regulation of Adipogenesis

Abstract: The activation of G protein-coupled receptor 103 (GPR103) by its endogenous peptidic ligands, QRFPs, is involved in the central regulation of feeding by increasing food intake, body weight, and fat mass after intracerebroventricular injection in mice. However, the role of GPR103 in regulating peripheral metabolic pathways has not yet been explored. The present study aimed to investigate the role of GPR103 in adipogenesis and lipid metabolism using 3T3-L1 adipocyte cells. Our results show that differentiated 3T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 47 publications
2
43
0
3
Order By: Relevance
“…Interestingly, in a previous study, GPR103 was also detected in epididymal fat pads and shown to be elevated by 16-fold in high-fat mice (32). In addition, these authors showed, using 3T3-L1 adipocyte cells, that 26RFa elicits a dose-dependent increase in fatty acid uptake and increases the expression of genes involved in lipid uptake as well as triglyceride accumulation (32).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, in a previous study, GPR103 was also detected in epididymal fat pads and shown to be elevated by 16-fold in high-fat mice (32). In addition, these authors showed, using 3T3-L1 adipocyte cells, that 26RFa elicits a dose-dependent increase in fatty acid uptake and increases the expression of genes involved in lipid uptake as well as triglyceride accumulation (32).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, QRFP expression in b-cells and human islets may suggest autocrine/paracrine effects of the peptides. Accordingly, 26RFa autocrine/paracrine effects have been recently proposed in prostate cancer cells, where the peptide induced cell migration and neuroendocrine differentiation, and in macrophages and adipocytes, where both 43RFa and 26RFa promoted adipogenesis (10,11,22). Future studies will help elucidate whether autocrine/paracrine mechanisms may also occur in pancreatic islets.…”
Section: Discussionmentioning
confidence: 93%
“…In humans and rodents, 43RFa, 26RFa, and GPR103 are mainly expressed in brain, particularly in the hypothalamus (8), as well as in peripheral tissues, including the eye, testis, thyroid, adipose tissue, and macrophages (6,(9)(10)(11). 43RFa and 26RFa have been implicated in many physiological functions, including stimulation of food intake (5,(12)(13)(14)(15)(16)(17), regulation of gonadotropic axis (18,19), aldosterone secretion (7,20), bone formation (21), adipogenesis and inflammation (10,11), blood pressure (12), and prostate cancer differentiation and migration (22).…”
mentioning
confidence: 99%
“…In the rat pancreas, glucose-evoked insulin secretion is reduced by perfusion of 26RFa/QRFP (Egido et al 2007). In the adipocyte cell line 3T3-L1, 26RFa/QRFP inhibits isoproterenol-induced lipolysis (Malumba et al 2010). As 3T3-L1 cells express the QRFPR-encoding gene, it appears that 26RFa/QRFP may act in an autocrine/paracrine manner to regulate adipogenesis (Malumba et al 2010).…”
Section: Comparative Aspects Of Biological Actions Of 26rfa/qrfp In Vmentioning
confidence: 99%
“…In the adipocyte cell line 3T3-L1, 26RFa/QRFP inhibits isoproterenol-induced lipolysis (Malumba et al 2010). As 3T3-L1 cells express the QRFPR-encoding gene, it appears that 26RFa/QRFP may act in an autocrine/paracrine manner to regulate adipogenesis (Malumba et al 2010). According to Alonzeau et al (2013), 26RFa/QRFP is also expressed in human prostate cancer and stimulates the neuroendocrine differentiation and migration of cancer cells.…”
Section: Comparative Aspects Of Biological Actions Of 26rfa/qrfp In Vmentioning
confidence: 99%